[OP.1A.04] 24H AMBULATORY BLOOD PRESSURE MONITORING PROFILE IN PARKINSON'S DISEASE WITH AUTONOMIC NEUROPATHY. (September 2016) - Milazzo, V.; Di Stefano, C.; Vallelonga, F.; Sobrero, G.; Milan, A.; Zibetti, M.; Sarchioto, M.; Romagnolo, A.; Lopiano, L.; Veglio, F.; Maule, S.
Abstract : Objective: Patients with Autonomic Neuropathy (AN) are characterized by orthostatic hypotension (OH), supine hypertension, high blood pressure (BP) variability and reverse dipping pattern on 24 h Ambulatory Blood Pressure Monitoring (24 h ABPM). AN is a common finding in Parkinson's disease (PD), and it is related to a higher motor impairment due to neurogenic OH. Aim of the study was the evaluation of the prevalence of AN and the assessment of the related 24 h ABPM profile in PD patients without known cardiovascular comorbidities. Design and method: 79 patients with PD and without known cardiovascular diseases were studied (mean age 63.2 ± 10.3 years; 67% males). None of the patients suffered from hypertension, diabetes, dyslipidemia, chronic kidney disease, and sleep apnea, and they were not treated with antihypertensive or antihypotensive drugs. Patients underwent cardiovascular autonomic reflex tests (deep breathing, lying to standing, Valsalva maneuver, and postural BP), and AN was defined by the presence of at least two pathological tests. On the same day, they underwent 24 h ABPM. 24 h ABPM dipping patterns were defined according to day-night BP difference (<0%: reverse dipping; 0–10%: non dipping; >10%: dipping). Nocturnal hypertension was defined as night-time systolic and diastolic BP > = 120/70 mmHg. Results: Results. Prevalence of AN was 29%. PD patients with AN were older (68.8 ± 10.1 vs 63.2 ± 10.3 years, p = 0.003) and had a higher prevalence of OH (78% vs 25%, p < 0.001). 24-h mean BP values were similar in patients with and without AN, while night-time BP values were higher (125 ± 17/73 ± 13 vs 111 ± 13/64 ± 11 mmHg, p < 0.05) and prevalence of nocturnal hypertension was higher (65% vs 36%, p = 0.016) in AN. Prevalence of reverse dipping pattern was much higher in patients with AN (74% vs 13%, p < 0.001) and they were characterized by a higher BP variability (SD of night-time SBP: 11.0 ± 4.1 vs 9.0 ± 2.9 mmHg, p = 0.048). Conclusions: PD patients with AN and without known cardiovascular diseases have a high prevalence of reverse dipping pattern and nocturnal hypertension. 24 h ABPM may represent a useful diagnostic tool in the diagnostic management of AN in PD patients.